Detection of Emerging Infectious Disease in Cynopterus brachyotis and Rhinolopus boorneensis as Reservoirs of Zoonotic Diseases in Indonesia - Moch. Irfan Hadi1 , Munawir1 , Muhammad Yusuf Alamudi2 , Dedi Suprayogi1 , Mirna Widiyanti3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Bats are mammal species that have the highest diversity. During the last two decades, various types of infections caused by microorganisms have again become epidemic in many countries, this phenomenon is known as a new infectious disease that arises and re-emerges or Re-Emerging Infectious Diseases (EID/ REID). The purpose of this study was to identify EID in bats in the karst area of South Malang. The research method of bat sampling is conducted in the karst area of South Malang, bats are identified by species, taken by blood, prepared and carried out by NGS (next generation sequencing). From the results of the research conducted, obtained 2 types of bats namely fruit-eating bats (Chiroptera brachjatis) and insect bats (Rhinolopus boorneensis). From the results of the NGS, we get specific viruses and bacteria in bats. The conclusion of this research is that bat in South Malang Karst has potential as a carrier of EID and zoonotic disease.